DESIGN AND DEVELOPMENT OF THERMAL CONDUCTIVITY DETECTOR - Yusoff, Yurahafcan (Universiti Teknologi Petronas, 2006)
Emerging need for a safe and healthy living nowadays lead to this project of gas detection. The main target of the project is to construct a thermal conductivity gas detector for environment monitoring. A gas detector which can detect potentially hazardous gases released to the environment. If the air composition is different from the normal, the thennal conductivity of gas detector should changeto detect and give a warning alarm to the people. A heat sensing circuit is employed here for this purpose, which by comparing the thermal conductivity of a potentially hazardous gas with normal air gives a warning signal. The literature review presents various methods of gas detection used these days. The methodology section gives detail design and development process taken in this project. The result is a practical heat detection circuit that is constructed, tested and calibrated with respect to normal air. It gives an indication of abnormality through bar graph display used in dot mode. Additionally, the project cost has been kept as low as possible.